2022
DOI: 10.1108/apjba-07-2021-0307
|View full text |Cite
|
Sign up to set email alerts
|

Corporate integrity, external assurance and sustainability reporting quality: evidence from the Malaysian public listed companies

Abstract: PurposeThis paper aims to examine the effect of corporate integrity and external assurance on Sustainability Reporting Quality (SRQ) of Malaysian public listed companies.Design/methodology/approachThe study uses a longitudinal sample of 2,463 firm-year observations of non-financial firms listed on the main board of Bursa Malaysia from 2015 to 2019. The study employed panel regression that is, Fixed Effect (FE) Robust Standard Error estimation technique to test its hypotheses.FindingsThe panel regression result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 112 publications
0
7
0
6
Order By: Relevance
“…Strategic influence encompasses the company's interactive functions with stakeholders in a timely and reliable transfer of news and information. This reduces the information asymmetry and creates trust and confidence in them (Elaigwu et al, 2022). By confirming this point, Garrett et al (2014) stated that increasing corporate integrity would result in further content conformity between the strategies and performances of the company concerning information sharing, and this can reduce information asymmetry through the quality of financial reporting.…”
Section: Corporate Integrity and Information Asymmetrymentioning
confidence: 82%
“…Strategic influence encompasses the company's interactive functions with stakeholders in a timely and reliable transfer of news and information. This reduces the information asymmetry and creates trust and confidence in them (Elaigwu et al, 2022). By confirming this point, Garrett et al (2014) stated that increasing corporate integrity would result in further content conformity between the strategies and performances of the company concerning information sharing, and this can reduce information asymmetry through the quality of financial reporting.…”
Section: Corporate Integrity and Information Asymmetrymentioning
confidence: 82%
“…The study of SR in emerging markets is a growing area of research. This is largely due to the unique challenges and opportunities presented by these markets that differ from those in more mature economies [33][34][35][36].…”
Section: Uniqueness Of Sustainability Reporting In Chinamentioning
confidence: 99%
“…Sustainability reporting is a form of information disclosure that illustrates firm's contribution to sustainability through economic, environmental, social activities (Elaigwu et al, 2022). Firms nowadays are aware of the commercial benefits of increased accountability (Sreepriya et al, 2022) and thus engage more in sustainability reporting (Aras and Crowther, 2009) thanks to the increasing need for transparency on economic, environmental, and social issues throughout the world (Buallay, 2019).…”
Section: Sustainability Reporting and Bank's Market Valuationmentioning
confidence: 99%
“…Firms nowadays are aware of the commercial benefits of increased accountability (Sreepriya et al, 2022) and thus engage more in sustainability reporting (Aras and Crowther, 2009) thanks to the increasing need for transparency on economic, environmental, and social issues throughout the world (Buallay, 2019). Prior studies have suggested to invest in sustainability reporting as a strategy (Ching and Gerab, 2017;Elaigwu et al, 2022) as it has been evidenced to able to create legitimacy and trust (Ching and Gerab, 2017;Shamil et al, 2014) that further deliver positive values to its reporting entity (Berthelot et al, 2012). Thus, firms can earn benefit from sustainability reporting practice to improve their image (Titisari et al, 2019).…”
Section: Sustainability Reporting and Bank's Market Valuationmentioning
confidence: 99%
See 1 more Smart Citation